2022
DOI: 10.24071/suksma.v3i2.5284
|View full text |Cite
|
Sign up to set email alerts
|

Dunia Simbolik: Ruang bagi Pemaknaan dan Kesadaran

Abstract: Apa itu ilmu psikologi? Pertanyaan semacam ini cukup lazim di antara akademisi psikologi. Pertanyaan ini terus menerus muncul dalam sejarah psikologi, seolah-olah para peneliti dan akademisi psikologi tidak pernah merasa kerasan tinggal di rumahnya sendiri. Seperti seseorang yang mendiami rumah baru, beberapa tampak asing dan beberapa tampak familiar, namun selalu timbul perasaan ada yang tidak cocok. Orang awam dengan mudah menyebutkan psikologi sebagai ilmu jiwa dengan merunut pada etimologinya, psike, namun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Lebih jauh lagi, menulis sejarah nasional dinilai bukan sekedar aktivitas intelektual melainkan juga bermakna politis (Henk Schule Nordholt dan Saptari, 2008). Selain itu narasi sosial secara psikologis juga sangat terkait dengan "cultural turn" yang hidup di masyarakat pada tiap zaman (Hartoko & Harimurti, 2021). Kenyataan tersebut pada akhirnya akan sangat mempengaruni pola dan orientasi narasi yang disajikan dalam buku teks sejarah.…”
Section: Pendahuluanunclassified
“…Lebih jauh lagi, menulis sejarah nasional dinilai bukan sekedar aktivitas intelektual melainkan juga bermakna politis (Henk Schule Nordholt dan Saptari, 2008). Selain itu narasi sosial secara psikologis juga sangat terkait dengan "cultural turn" yang hidup di masyarakat pada tiap zaman (Hartoko & Harimurti, 2021). Kenyataan tersebut pada akhirnya akan sangat mempengaruni pola dan orientasi narasi yang disajikan dalam buku teks sejarah.…”
Section: Pendahuluanunclassified
“…Introducing and conveying the wisdom of English dialects to preschool and elementary school children is not an easy thing (Dony Novaliendry & Andriani, 2020; Rahmasari et al, 2022). at this age are generally still unable to understand everyday dialect (Indonesian) (Suparman, 2022), This makes it difficult for children to accept the presence of languages other than everyday language (Hartoko, 2022). According to Putri et al (Putri & Sya, 2022) in their research, it was revealed that age does not affect the rhythm of learning, but it greatly influences the average speed of learning a second language and there is a need for programs that can help students to achieve their learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing and conveying the wisdom of English dialects to preschool and elementary school children is not an easy thing (Dony Novaliendry & Andriani, 2020; Rahmasari et al, 2022). at this age are generally still unable to understand everyday dialect (Indonesian) (Suparman, 2022), This makes it difficult for children to accept the presence of languages other than everyday language (Hartoko, 2022). According to Putri et al (Putri & Sya, 2022) in their research, it was revealed that age does not affect the rhythm of learning, but it greatly influences the average speed of learning a second language and there is a need for programs that can help students to achieve their learning goals.…”
Section: Introductionmentioning
confidence: 99%